From Classroom to Diplomacy: Reflections on BIPA Teaching by Timorese Teachers - Soares, Rodolfo Soares; Latifah, Diah; Sulistiany Idris, Nuny (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to explore the experiences of local educators teaching Indonesian as a Foreign Language (BIPA) in Timor-Leste, specifically at two educational institutions: Escola Secundaria Geral (ESG) and Escola Técnica Vocacional (ESTV). Using a reflective qualitative approach with a collective case study design, the research involved six active teachers as key participants. Data were gathered through classroom observations, semi-structured interviews, open-ended questionnaires, and analysis of instructional documents, then examined using thematic coding and narrative reflection. The findings show that teachers developed task-based learning strategies, culturally relevant media, and contextual approaches despite facing structural limitations. Lesson plans generally demonstrated moderate alignment with Graduate Competency Standards (SKL), though they need improvement in goal setting, cultural integration, and rubric-based assessment. This study emphasizes teachers’ voices as essential sources of curricular knowledge, shifting focus from macro-level policy to reflective classroom practice. Consequently, BIPA is seen not just as a language teaching initiative but as a form of soft diplomacy that strengthens bilateral relations between Indonesia and Timor-Leste through intercultural education.